Delta Mekonga - dežela riža in vodnih prekopov - Zabukovec, Blaž (Geografski obzornik, 1997)
Mekong river delta on the southern part of Vietnam is country's rice basket. Due to its economical importance it creates the fortune for the whole country. The south-east Asia'a giant river dictates the development pace of the province, which is one of the biggest rice growing regions in the world.
Keywords: Mekong; regionalna geografija; reke; Vietnam